2014
DOI: 10.1007/s00246-014-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of Clinical Biomarkers, Use of Inotropic Medications and Fluid Resuscitation in Newborns with Persistent Pulmonary Hypertension

Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is associated with high morbidity and mortality. This study evaluated clinical outcomes in PPHN in relation to echocardiographic (EC) markers, score of neonatal acute physiology, perinatal extension, version II (SNAPPE II) scores, inotropic agent use, and the amount of fluid received as boluses. In this retrospective chart analysis of 98 neonates with PPHN born at >34 weeks' gestation, we compared two cohorts of newborns: those who received inhaled nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…There are no randomised studies primarily designed to examine fluid bolus compared to no fluid bolus in preterm infants with haemodynamic compromise . Studies in late preterm and term infants with haemodynamic compromise are limited to non‐randomised observational studies and do not report clinical benefit . A survey in Canada reported that, while attitudes to the use of inotropes varied, neonatologists routinely treated suspected haemodynamic compromise in infants with a birthweight <1500 g with a fluid bolus (97%) and most commonly used 0.9% sodium chloride (95%) .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…There are no randomised studies primarily designed to examine fluid bolus compared to no fluid bolus in preterm infants with haemodynamic compromise . Studies in late preterm and term infants with haemodynamic compromise are limited to non‐randomised observational studies and do not report clinical benefit . A survey in Canada reported that, while attitudes to the use of inotropes varied, neonatologists routinely treated suspected haemodynamic compromise in infants with a birthweight <1500 g with a fluid bolus (97%) and most commonly used 0.9% sodium chloride (95%) .…”
Section: Discussionsupporting
confidence: 78%
“…15 Studies in late preterm and term infants with haemodynamic compromise are limited to non-randomised observational studies and do not report clinical benefit. 16,17 A survey in Canada reported that, while attitudes to the use of inotropes varied, neonatologists routinely treated suspected haemodynamic compromise in infants with a birthweight <1500 g with a fluid bolus (97%) and most commonly used 0.9% sodium chloride (95%). 18 Our results are consistent with this, with the majority of fluid boluses (47/56; 84%) given to an infant to manage low blood pressure being 0.9% sodium chloride.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial infection was diagnosed based on either the presence of bacteria in the cerebrospinal fluid or a combination of pleocytosis >29 cells/mm 3 , protein >1.5 g/L and glucose <2.2 mmol/L, or cerebrospinal fluid/blood glucose ratio <0.5. Persistent pulmonary hypertension of the newborn was diagnosed using echocardiogram parameters and by assessing the difference between preductal and post‐ductal saturations . Patent ductus arteriosus (PDA) was defined according to echocardiography .…”
Section: Methodsmentioning
confidence: 99%
“…Only two primary studies1 2 are currently available to assist in assessing whether fluid bolus therapy in preterm and term infants has any objective clinical benefit. No relevant randomised controlled trials were identified.…”
Section: Commentarymentioning
confidence: 99%
“…The two identified studies were retrospective studies with comparator groups 3. These studies found that receipt of fluid bolus therapy was likely to be a marker of illness severity rather than a cause of adverse effects in infants with persistent pulmonary hypertension of the newborn1 and hypoxic-ischaemic encephalopathy 2. One of the excluded studies, examining the use of fluid bolus therapy in infants with gastroschisis, found that every additional 17 mL/kg of intravenous fluid was associated with adverse clinical outcomes 3.…”
Section: Commentarymentioning
confidence: 99%